Hebraic republican exclusivism: An assessment of Eric Nelson's argument. (February 2016) - McDougall, Derek
Eric Nelson in The Hebrew Republic argues that a revival of Hebraic studies in 17th-century England led to the emergence of a republican exclusivism, exemplified particularly in the work of John Milton. Thomas Hobbes and Baruch Spinoza went to lengths to reject the exclusivist argument. Republican exclusivism had some impact in the English Revolution, and was also an influence in the American Revolution, mainly through the advocacy of Thomas Paine. British-American models of government, incorporating the 'republican' dimension in different ways, have subsequently had a significant influence in many parts of the world. Whether republican exclusivism has been the major theme in modern political thought is more debatable; it is contended that social contract theory in various forms has been more significant.